FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KECEMASAN IBU DALAM PEMBERIAN IMUNISASI DPT PADA BAYI - Hatta Novika, Revi Gama; Sriyanah, Nour; Sermoati, Inmas Andi; Agustini, Meti; Shahab, Fatinah (Ensiklopedia of Journal, 2024)
Immunization is an effort to prevent infectious diseases by giving vaccines so that immunity (immunity) to the disease occurs. In 2022 the achievement of DPT immunization coverage at the Rokan Hilir Regency Puskesmas which has not reached the national target of 95%, one of which is the Bagan Punak health center 77.8%. Based on data, the DPT I, II and III munization coverage at the puskesmas has decreased to reach 77.9% in 2020, while in 2021 the DPT I, II and III munization coverage reached 78, 6%, and in 2022 the DPT I, II and III immunization coverage only reached 79.9%, from the data obtained by the Bagan Punak Puskesmas, the lowest DPT immunization coverage was recorded in Labuhan Tangga Besar Village, namely 64.2%. while Bagan Punak Meranti Village is the village with the highest immunization coverage, namely 80.4%. The purpose of the study was to determine the factors associated with maternal anxiety in giving DPT immunization to infants in Labuhan Tangga Besar Village. This study used a quantitative analytic research design with a cross sectional study design. The sampling technique in this study was total sampling. The results of the study were that there was a relationship between knowledge (p value 0.000), attitude (p value 0.041) and family support (p value 0.000) on maternal anxiety in giving DPT immunization to infants in Labuhan Tangga Besar Village. It is recommended that the Puskesmas can conduct socialization, counseling, distribute brochures to mothers.Keywords: DPT Immunization, Knowledge, Attitude